MODEL SISTEM INFORMASI PEMBUKUAN UNTUK MONITORING TRANSAKSI KOPERASI DALAM MENDUKUNG PERHITUNGAN SISA HASIL USAHA - Deden Roni Nurjaman; Turki Salim; Risma Damayanti (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2019)
Cooperatives function to build and develop the potential economic capacity of members to improve economic and social welfare. Cooperatives are established aiming to realize the welfare of members in particular and the community at large and participate in building the national economic order in order to create an advanced, just and prosperous society based on Pancasila and the 1945 Constitution. Cooperatives organize several types of businesses such as savings and loans, all-round shops there and general trade. In running the business, the cooperative conducts bookkeeping to find out the profit / loss of the cooperative and the amount of the remaining business results that are fair and comparable to the amount of business services of each member. In the bookkeeping process there were often several problems such as, not well recorded every small and routine transaction, there were miscalculation caused by human error, the slow process of calculating the remaining business results which caused delays in making the report. To overcome this, it is necessary to design a bookkeeping information system model in the form of use case diagrams as a design model and class diagram as a database model and system application as a form of implementation, so that it isable to create a bookkeeping information system for monitoring cooperative transactions in supporting the calculation of the remaining results business effectively, efficiently, quickly and accurately.